Cyclase‐associated protein 1 is a key negative regulator of milk synthesis and proliferation of bovine mammary epithelial cells. (8th March 2019) - Yuan, Xiaohan; Zhen, Zhen; Zhang, Minghui; Yu, Yanbo; Gao, Xuejun; Ao, Jin‐xia
Abstract : Adenylyl cyclase‐associated protein (CAP) is a highly conserved protein. Previous reports have suggested that CAP1 may be a negative regulator of cellular proliferation, migration, and adhesion and the development of cell carcinomas. The molecular mechanism of CAP1 regulation of downstream pathways, as well as how CAP1 is regulated by environmental stimuli and upstream signalling, is not well understood. In this present study, we assessed the role of CAP1 in milk synthesis and proliferation of bovine mammary epithelial cells. Using gene overexpression and silencing methods, CAP1 was found to negatively regulate milk synthesis and proliferation of cells via the PI3K‐mTOR/SREBP‐1c/Cyclin D1 signalling pathway. Hormones, such as prolactin and oestrogen, and amino acids, such as methionine and leucine, stimulate MMP9 expression and trigger CAP1 degradation, and thus, abrogate its inhibition of synthesis of milk protein, fat, and lactose by and proliferation of bovine mammary epithelial cells. The results of our study help deepen our understanding of the regulatory mechanisms underlying milk synthesis and aid in characterizing the molecular mechanisms of CAP1. Previous reports have suggested that CAP1 is a negative regulator of cellular proliferation and anabolism, but the molecular mechanisms are largely unknown. In this present study, we identified CAP1 as a negative regulator of milk synthesis and proliferation of bovine mammary epithelial cells. Our results will deepen our understanding of the regulatory mechanisms underlying milk synthesis and aid in exploring the molecular mechanisms of CAP1.